When is retrieval protected?: Divided attention in different memory tasks - Vranić, Andrea (Array, 2009)
Divided attention at encoding is shown to reduce memory performance significantly, whereas division of attention during retrieval of episodic memories affects memory performance only minimally. This relative immunity of episodic retrieval is offset by a cost, as measured by the concurrent secondary task. Less is known on the effects a division of attention might have on the semantic retrieval. This experiment was conducted with the aim of further exploring the relative immunity and the attentional costs associated with what seems to be obligatory retrieval processes. A componential analysis, as introduced by Naveh-Benjamin et al. (2000), was employed to assess attentional demands of four different retrieval tasks: two tapping the episodic and two tapping the semantic memory system. Furthermore, within each of these „system tasks“, one task was data-driven and one was conceptually-driven, as proposed by the transfer-appropriate processing (TAP) approach. Our results show differential attentional demands of the four tasks used and further validate the pattern of 3 major retrieval types proposed by recent studies. These findings are interpreted within the TAP framework.